Pharaoh's Fury: Merneptah's Destruction of Gezer - Ortiz, Steven M. (Biblical archaeology review, 2022)
The article highlights that The merneptah stele which most scholars date to c.1208 B.C.E., provides the earliest reference to Israel outside the Bible. It also discusses that Gezer is located in the Aijalon Valley of the Judean foothills which and the site overlooks Israel's southern coastal plain, along which ran the ancient Via Maris, the major north-south route that led from Egypt to Mesopotamia, and the primary routes leading from the Mediterranean coast to the central hill country.